Intra- and Inter-week Variations of Well-Being Across a Season: A Cohort Study in Elite Youth Male Soccer Players - Nobari, Hadi; Fani, Maryam; Clemente, Filipe Manuel; Carlos-Vivas, Jorge; Pérez-Gómez, Jorge; Ardigò, Luca Paolo (Frontiers in Psychology, 2021)
This study describes the weekly variations of well-being ratings relative to fatigue (wFatigue), stress (wStress), delayed onset muscle soreness (wDOMS) sleep quality (wSleep) and Hooper questionnaire (wHQ) throughout the season. Also, compare well-being variables for the playing position in different moments of the season. Twenty-one elite young soccer players U17 took part in this study. From the beginning of the pre-season, well-being status was daily monitoring by the HQ method throughout 36 weeks (Four periods: 1. Pre-season, 2. Early-season, 3. Mid-season, and 4. End-season). Players trained, at least, three times per week throughout the season. The main outcome was that in week 33 and 28, the highest and the lowest wFatigue and wHQ occurred, respectively. Although, the low level of wDOMS happened in week 28, the highest wDOMS was observed in week 5 (13.00±1.79 AU). The highest wSleep (10.16±1.60 AU) and wStress (9.73±1.21 AU) were observed in week 8 and 34, respectively; while the lowest wSleep and wStress were remarked in week 29 coincidentally. In the HQ between every weekday, except recovery day, and the day of the match (MD) only revealed considerable highest HQ in 2 days after MD in contrast to overall team comparative. In the present study, we observed that well-being changes between different phases of the season as well as between weeks and days of the week with the MD are significant. Which means all result, provide great point of view for coaches' practitioners about well-being variations over a season in elite youth level and the feedback of that is the awareness of coaches about non-functional overreaching and taking measures to prevent it.